Green Synthesis and Characterization of Zinc Oxide Nanoparticles using Corchorus olitorius Leaf Extract - Kpega, Tyosue Christopher; Habila, James Dama; Okon*, Idongesit Edem; Ekwumemgbo, Patricia Adamma (Graduate School of Universitas Syiah Kuala, 2023)
Green synthesis of metal oxide nanoparticles has gained prominence in recent years, resulting from the absence of toxic chemicals, low energy requirement, and eco-friendliness. This paper reports the green synthesis of zinc oxide nanoparticles (ZnO-NPs) using plant extract as a reducing agent. The ZnO-NPs were synthesized using Corchorus olitorius leaf extract and zinc acetate dihydrate, Zn (CH3COO)2.2H2O as precursor. The synthesized ZnO-NPs were characterized by the application of UVVis spectroscopy, Transmission Electron Microscopy (TEM), X-ray diffraction (XRD), Energy Dispersive X-ray Spectroscopy (EDX) and Fourier Transform Infrared Spectroscopy (FTIR). UV-vis indicated the reduction of zinc acetate dihydrate into ZnO-NPs by the leave extract. XRD and TEM revealed that the average size of the synthesized ZnO-NPs was 22 nm. The XRD pattern showed the hexagonal wurtzite crystalline nature of the synthesized ZnO-NPs. The elemental composition obtained from EDX showed that the synthesized ZnO-NPs are primarily composed of three elements: Zn (75.20 %), O (20.48.7%), and C (4.32). Examination of stretching and bonding in the ZnO-NPs using FT-IR revealed the presence of Zn-O bonding at 430.37403.93 cm-1.